2023
DOI: 10.1007/s00431-023-05174-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serum insulin-like growth factor-1, fibroblast growth factor 23, and Klotho levels in girls with rapidly progressive central precocious puberty

Yuping Liu,
Yaying Cheng,
Meng Sun
et al.

Abstract: To study the levels of serum insulin-like growth factor 1 (IGF-1), fibroblast growth factor 23 (FGF23), and Klotho, and to study their relationship with girls with rapidly progressive central precocious puberty (RP-CPP). This is a cross-sectional study on the progression rate of central precocious puberty in girls, who complained of breast development before the age of 8 years and were followed between June 2021 and June 2022. At the same time, 28 healthy girls less than 8 years old who had not started puberty… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In addition, our multivariable logistic regression analysis for CPP revealed that α-Klotho is a significant factor influencing the outcome, similar to basal LH and estradiol. Furthermore, a previous study demonstrated the correlation between basal LH, FGF23, Klotho, and IGF-1 with rapidly progressive CPP, suggesting their potential importance in the rate of sexual development in girls ( 24 ). Building upon this body of literature and our own results, we hypothesized that an increase in LH, FSH, and IGF-1 levels during the onset of puberty may lead to higher α-Klotho levels.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, our multivariable logistic regression analysis for CPP revealed that α-Klotho is a significant factor influencing the outcome, similar to basal LH and estradiol. Furthermore, a previous study demonstrated the correlation between basal LH, FGF23, Klotho, and IGF-1 with rapidly progressive CPP, suggesting their potential importance in the rate of sexual development in girls ( 24 ). Building upon this body of literature and our own results, we hypothesized that an increase in LH, FSH, and IGF-1 levels during the onset of puberty may lead to higher α-Klotho levels.…”
Section: Discussionmentioning
confidence: 87%